Social Exclusion in the Education of Students with Religious Beliefs in Banyumas - Marselinus; Nasywa Andi Oosterdam; Calya Nashifa Adi Saputri; Faril Insan Madani; Fajar Widianto; Zidan Alfin Mubarrok; Tata Indra Wati (Universitas Negeri Yogyakarta, 2026)
Ministry of Education and Culture Regulation No. 27 of 2016 provides access for students who practice a particular faith to receive an education that is equal to that of their peers. This study describes the implementation of this regulation in Banyumas Regency and the forms of social exclusion in the implementation of this regulation. The research approach used is descriptive qualitative with data collection techniques through in-depth interviews, observation, and documentation. Informants in this study were determined using snowball sampling from students and education counsellors. Data analysis used the Miles and Huberman model. Data validity was obtained using researcher triangulation. The results show that since 2017, religious education has been implemented with support from MLKI and education counselors. The number of students who practice their beliefs has increased from 4 students initially to 10 students and 7 education counselors currently. However, the implementation process faces social exclusion barriers such as initial rejection of belief education, social stereotypes, forced use of certain religious symbols, and unequal access to textbooks, class placement, and assignments that conflict with students' beliefs in general subjects. This shows that there is still a dominance of the majority religion in the Indonesian education system. This study emphasizes the importance of socialization and enforcement of policies to guarantee equal education rights for students who practice beliefs. Therefore, the implementation of belief education requires collaboration from all parties in order to overcome obstacles and ensure that students can access education in accordance with their beliefs and human rights equally.